A pilot study of cognitive remediation in remitted major depressive disorder patients. Issue 2 (4th March 2022) - Hammar, Åsa; Semkovska, Maria; Borgen, Ida M. H.; Myklebost, Sunniva; Ronold, Eivind H.; Sveen, Thea; Ueland, Torill; Porter, Richard; Johnson, Sheri L.
Abstract: Major depressive disorder (MDD) is associated with working memory (WM) impairments. These deficits often persist following remission and are associated with rumination, a recognized risk factor for depression relapse. The efficacy of WM-targeted cognitive remediation as a potential relapse prevention tool has not been investigated. The present pilot study aimed to investigate the feasibility, acceptability, and cognitive benefits of a WM-targeted cognitive remediation program in remitted depression. Twenty-eight MDD participants in remission were recruited. The intervention consisted of twenty-five 30–40-minute training sessions, coupled with weekly coaching, administered over a 5-week period. Before and after the intervention, a battery of objective neuropsychological tests and self-report measures was administered. Key outcomes were WM, inhibition and rumination. Acceptability of the intervention was observed, with 83% showing high motivation, along with WM gains for all completers ( n =  18, 64% of recruited participants). The cognitive remediation selectively improved targeted WM functions, as measured by objective tests. This did not translate into self-reported improvements in everyday WM or inhibition. However, all but one completer achieved at least one personal goal related to WM and 44% achieved two or, the maximum possible, three such goals. For remitters whose WM was significantly enhanced after the intervention, the cognitive remediation also decreased dysphoric-mood related rumination. The successful pilot testing of the WM-targeted intervention supports the conduct of a fully powered randomized controlled trial as a relapse prevention approach in remitted MDD.